Effect of home-bleaching gels modified by calcium and/or fluoride and the application of nano-hydroxyapatite paste on in vitro enamel erosion susceptibility - Santos, Luciana Floriani Thives Freitas [UNESP]; Torres, Carlos Rocha Gomes; Caneppele, Taciana Marco Ferraz; Magalhães, Ana Carolina; Borges, Alessandra Buhler (Acta Odontologica Scandinavica, 2015)
This in vitro study compared the effect of bleaching agents modified by the addition of calcium and/or fluoride and the application of a nano-hydroxyapatite paste after bleaching, on the susceptibility of enamel to erosion. Bovine enamel cylindrical samples (3 mm diameter) were assigned to six groups (n = 20 specimens/group) according to the bleaching agent: no bleaching (C-control), 7.5% hydrogen peroxide gel (HP), HP with 0.5% calcium gluconate (HP+Ca), HP with 0.2% sodium fluoride (HP+F), HP with calcium and fluoride (HP+Ca+F) and HP followed by the application of a nano-hydroxyapatite agent (HP+NanoP). The gels were applied on the enamel surface (1 h) followed by cyclic erosive challenges (Sprite Zero®-2 min), for 14 days. The paste was applied after bleaching for 5 min (HP+NanoP). The enamel surface alteration was measured by contact profilometry (µm) (after 7 and 14 days). C-control (mean ± SD: 2.29 ± 0.37 at 7 days/4.86 ± 0.72 at 14 days) showed significantly lower loss compared to the experimental groups. HP+Ca (3.34 ± 0.37/6.75 ± 1.09) and HP+F (4.49 ± 0.92/7.61 ± 0.90) presented significantly lower enamel loss than HP (4.18 ± 0.50/10.30 ± 1.58) only for 14 days and HP+Ca+F (4.92 ± 1.03/8.12 ± 1.52) showed values similar to the HP+F group. The HP+NanoP (5.51 ± 1.04/9.61 ± 1.21) resulted in enamel loss similar to the HP after 14 days. It was found that 7.5% hydrogen peroxide increased the susceptibility of enamel to erosion. The addition of calcium or fluoride to the bleaching gel reduced the erosion effect, while the nano-hydroxyapatite agent did not provide any protective effect.
Keywords: Enamel; Erosion; Hydrogen peroxide; Tooth bleaching; Tooth wear